PERBANDINGAN PENERAPAN INQUIRY BASED LEARNING PADA PEMBELAJARAN SAINS SMP DI THAILAND DAN INDONESIA - Citra Mashita; Murni Ramli; Puguh Karyanto (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2018)
Inquiry based learning (IBL) has become a prominent learning model in science educational reform in all countries. This research is a comparative studies which aims to analyse the practices of inquiry based learning in the science class of one Junior High School (JHS) in Thailand and Indonesia as part of the Sea-Teacher Project conducted by SEAMEO. The subjects were selected by convenience sampling, teachers and students grade 1, 2, and 3 of Chiang Rai Municipality School 6, also teacher and VIII-F students’ of Junior High School 4 Surakarta. Data were collected by document analysis of science curriculum, syllabus, lesson plans, and assessment; classroom observations, field notes, photo, video recordings; and interviews to teachers. The research confirmed that IBL has been adopted in the lower secondary science curriculum in both countries. Teachers have perception that science is about process, value, and product. Science is also about conservation and human existence. Syllabus and lesson plans of both school have followed the steps of IBL. Science learning activities show that both schools are in the same inquiry level, structured inquiry. Assessment of science learning is dominated by conceptual knowledge dimension, with different cognitive dimension processes. Thailand school has a higher level C3 (apply), while Indonesia is dominated by C1 (recall).Keywords: comparative studies,inquiry based learning, science learning, Thailand, Indonesia